Zn coatings for temporary protection applied by peening technology - Brezinnová, Janette (Journal of Metals, Materials and Minerals, 2017)
This paper presents actual investigation results of an experiment that aimed at verifying the possibility of applying zinc on steel surface by peening technology using zinc-coated cut wire. A suitable method for obtained zinc layers and evaluation of their corrosion resistance was determined. Accelerated laboratory tests with presence of SO2 and long term working tests in atmospheric conditions were used. Creation of incoherent zinc coatings was established on the bases of metallographic and spectral analysis. The process of cold zinc by peening may serve as temporary anticorrosion protection of steel surface.